THE EXPRESSION OF THE ENDOGENOUS METABOLIC INTOXICATION SYNDROME AND LIPID PEROXIDATION IN THE PATIENTS WITH ESSENTIAL HYPERTENSION IN COMBINATION WITH DUODENAL PEPTIC ULCER IN DIFFERENT TERMS OF OUTPATIENT OBSERVATION AND TREATMENT - Burmak , Yurii; Petrov , Yevhen; Ivanytska , Tetiana; Іvanytskyi , Іgor (Collection of scientific papers «ΛΌГOΣ», 2023)
Now the role of endogenous intoxication syndrome (EIS) as the cause of non-specific manifestations of many diseases is known [1, 2]. The role of lipid peroxidation (LP) as a factor in the formation of internal organs’ pathology is also well known [3]. The results of the study established their role and ways of influence, including on the formation and course of diseases of the cardiovascular and digestive systems [3, 4, 5, 6]. It is possible to predict that comorbid conditions accompany metabolic disorders, which are characterized by the presence of certain their features.